Respuesta :

Answer:

x=3±√23

thats the answer ^^

Step-by-step explanation:

plz give me brainlyest i need it

Answer:

Option 1

Step-by-step explanation:

[tex]3 {x}^{2} - 18x + 5 = 47[/tex]

[tex] = > 3 {x}^{2} - 18x + 5 - 47 = 0[/tex]

[tex] = > 3 {x}^{2} - 18x - 42 = 0[/tex]

[tex] = > 3( {x}^{2} - 6x - 14) = 0[/tex]

[tex] = > {x}^{2} - 6x - 14 = 0[/tex]

We know that

[tex]x = \frac{ - b + \sqrt{d} }{2a} \: or \: \frac{ - b - \sqrt{d} }{2a} [/tex]

Where D = Discriminant of the eqn.

Discriminant of the above eqn.=

[tex] {b}^{2} - 4ac = {( - 6)}^{2} - 4 \times ( - 14) \times 1 = 92[/tex]

So,

[tex]x = \frac{ - ( - 6) + \sqrt{92} }{2 \times 1} \: or \: \frac{ - ( - 6) - \sqrt{92} }{2 \times 1} [/tex]

[tex] = > x = \frac{6 + 2 \sqrt{23} }{2} \: or \: \frac{6 - 2 \sqrt{23} }{2} [/tex]

[tex] = > x = (3 + \sqrt{23} ) \: or \: (3 - \sqrt{23} )[/tex]

ACCESS MORE